Kaurane-Type Diterpenoids as Potential Inhibitors of Dihydrofolate Reductase-Thymidylate Synthase in New World Leishmania Species - Chonny Herrera-Acevedo; Renata Priscila Barros de Menezes; Natália Ferreira de Sousa; Luciana Scotti; Marcus Tullius Scotti; Ericsson Coy-Barrera (MDPI AG, 2023)
The bifunctional enzyme Dihydrofolate reductase-thymidylate synthase (DHFR-TS) plays a crucial role in the survival of the Leishmania parasite, as folates are essential cofactors for purine and pyrimidine nucleotide biosynthesis. However, DHFR inhibitors are largely ineffective in controlling trypanosomatid infections, largely due to the presence of Pteridine reductase 1 (PTR1). Therefore, the search for structures with dual inhibitory activity against PTR1/DHFR-TS is crucial in the development of new anti-Leishmania chemotherapies. In this research, using the Leishmania major DHFR-TS recombinant protein, enzymatic inhibitory assays were performed on four kauranes and two derivatives that had been previously tested against LmPTR1. The structure 302 (6.3 µM) and its derivative 302a (4.5 µM) showed the lowest IC50 values among the evaluated molecules. To evaluate the mechanism of action of these structures, molecular docking calculations and molecular dynamics simulations were performed using a DHFR-TS hybrid model. Results showed that hydrogen bond interactions are critical for the inhibitory activity against LmDHFR-TS, as well as the presence of the p-hydroxyl group of the phenylpropanoid moiety of 302a. Finally, additional computational studies were performed on DHFR-TS structures from Leishmania species that cause cutaneous and mucocutaneous leishmaniasis in the New World (L. braziliensis, L. panamensis, and L. amazonensis) to explore the targeting potential of these kauranes in these species. It was demonstrated that structures 302 and 302a are multi-Leishmania species compounds with dual DHFR-TS/PTR1 inhibitory activity.